A randomized phase II trial of hepatic arterial infusion of oxaliplatin plus raltitrexed versus oxaliplatin plus 5-fluorouracil for unresectable colorectal cancer liver metastases - Feng, Ai-Wei; Guo, Jian-Hai; Gao, Song; Kou, Fu-Xin; Liu, Shao-Xing; Liu, Peng; Chen, Hui; Wang, Xiao-Dong; Xu, Hai-Feng; Cao, Guang; Zhu, Xu (Frontiers in Oncology, 2022)
Background The purpose was to compare the efficacy and safety of hepatic arterial infusion (HAI) of oxaliplatin plus raltitrexed (TOMOX) to those of oxaliplatin plus 5-fluorouracil (FOLFOX) for unresectable colorectal cancer liver metastases (CRCLM). Methods Patients with unresectable CRCLM were randomly assigned to receive HAI of TOMOX or FOLFOX. The primary end points were progression-free survival (PFS) measured from the date of randomisation until the date of disease progression and objective response rate (ORR). The secondary end points were overall survival (OS) measured from the date of randomisation until the date of death from any cause, disease control rate (DCR), and adverse events. Results 113 patients were randomly assigned. With a median follow-up of 39.5 months, the PFS was 5.8 months [95% CI, 4.838–6.762]) and 4.6 months [95% CI, 3.419–5.781; P = 0.840], and the median OS was 17.6 months [95% CI, 13.828–21.372] and 13.1 months [95% CI, 11.215–14.985; P = 0.178] for the FOLFOX and TOMOX arm, respectively. The ORR were 26.1% vs 22.4% and DCR were 80.4% vs 71.4% in the FOLFOX and TOMOX arms. The most common severe adverse event was elevation of liver enzymes and pain, which did not differ in the two arms. Conclusion HAI chemotherapy was effective for unresectable CRCLM. HAI of FOLFOX has similar efficacy to TOMOX, and HAI of TOMOX had shorter arterial infusion time. Clinical Trial Registration https://clinicaltrials.gov/, identifier NCT02557490.